Self-Harm and Suicide Attempts among High-Risk, Urban Youth in the U.S.: Shared and Unique Risk and Protective Factors - Swahn, Monica H. (MDPI, 2012)
The extent to which self-harm and suicidal behavior overlap in community samples of vulnerable youth is not well known. Secondary analyses were conducted of the “linkages study” (N = 4,131), a cross-sectional survey of students enrolled in grades 7, 9, 11/12 in a high-risk community in the U.S. in 2004. Analyses were conducted to determine the risk and protective factors (i.e., academic grades, binge drinking, illicit drug use, weapon carrying, child maltreatment, social support, depression, impulsivity, self-efficacy, parental support, and parental monitoring) associated with both self-harm and suicide attempt. Findings show that 7.5% of participants reported both self-harm and suicide attempt, 2.2% of participants reported suicide attempt only, and 12.4% of participants reported self-harm only. Shared risk factors for co-occurring self-harm and suicide attempt include depression, binge drinking, weapon carrying, child maltreatment, and impulsivity. There were also important differences by sex, grade level, and race/ethnicity that should be considered for future research. The findings show that there is significant overlap in the modifiable risk factors associated with self-harm and suicide attempt that can be targeted for future research and prevention strategies.